The Use Of Regenerative Practices In A Company’s Daily Operation In Enhancing Ecosystem-Wide Flourishing - Amanda Shafa Wiriawan; Agung Juliarto; Frank Gruben (Diponegoro Journal of Accounting, 2025)
The research explores the integration of regenerative practices in daily business operations, focusing on their potential to enhance ecosystem-wide flourishing. It uses Foodvalley NL as a case study to examine the financial, operational, and ecological benefits of these practices. The study uses a mixed-methods approach, combining qualitative interviews with industry stakeholders and quantitative analysis of financial and operational data. The findings show that regenerative practices can drive systemic change by creating positive feedback loops that enhance ecosystem health, stakeholder well-being, and organizational resilience. Despite challenges like high initial costs and knowledge gaps, the study identifies strategic solutions, such as cross-sector collaboration and scalable frameworks, to support businesses in adopting regenerative methods. The research concludes that regenerative practices offer transformative pathways for businesses to achieve financial sustainability while contributing to environmental restoration and social equity.